American kingpin : the epic hunt for the criminal mastermind behind the Silk Road - Bilton, Nick (Portfolio/Penguin, 2017)
From New York Times-bestselling author Nick Bilton comes a true-life thriller about the rise and fall of Ross Ulbricht, aka the Dread Pirate Roberts, the founder of the online black market Silk Road.